Retraction: [Systematic Investigation of Selected Bio-molecules Potentially Effective in Inhibiting SARS-CoV-2/COVID-19 via In-Silico Analysis] - Vanzara, Akash; Ambasan, Saloni; Shrivastav, Amit; Patel, Swati; Patel, Vishal; Soni, Hardik; Trivedi, Vikram (Fine Chemical Engineering, 2024)
Retraction Note: Volume 6 Issue 1, FCE-6482 DOI: https://doi.org/10.37256/fce.6120256482 There have been millions of cases of Coronavirus, Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) with high infectious properties during the year 2019. To counter the situation, certain medications were prescribed by health experts, such as Remdesivir, Dexamethasone, Azithromycin and Hydroxychloroquine, following the World Health Organization (WHO) guidelines. While vaccines have since been administered to alleviate symptoms, alternative treatments like Ayurvedic remedies are being explored. This study specifically delves into in-silico analysis using Autodock 4.2.6 software to assess selected phytomarkers against the 6LU7 main protease protein. The chemical structures of these drugs were analyzed using SWISSADME software to evaluate their drug-likeness properties. Molecular docking was conducted using Autodock tools 1.5.6, and receptor-ligand interactions were visualized using PyMol 2.3. Discovery Studio Visualizer 2020 generated a two-dimensional map illustrating bond interactions and distances between drugs and receptors. The mean binding energies of the compounds, including Nobiletin, Tangeretin, Sideroxylonal C, Coriandron, Epicatechin, Epigallocatechin gallate, Luteolin, Ombuin, Tamarixetin, 6-deacetylnimbin, Nimbolide, and Tricin were -5.66, -6.00, -6.46, -6.40, -6.91, -6.51, -6.34, -6.46, -6.99, -6.82, -6.51, -7.85, and -6.35 kcal/mol. Notably, several bioactive markers, including Nobiletin, Tangeretin, Epicatechin, Epigallocatechin gallate (EGCG), Ombuin, Tamarixetin, and Nimbolide, exhibited similar binding sites to synthetic drugs like Remdesivir, such as PHE140, CYS145, GLU166, and GLN189. The investigation also addresses Absorption, Distribution, Metabolism, Excretion, and Toxicity (ADMET) modelling, binding energy scores, and binding affinity, emphasizing the importance of vaccination as a crucial measure to curb the spread of infection.